Effects of habitat fragmentation on the reproductive ecology of Quararibea ochrocalyx (K. Schum) Vischer in the tropical humid forest of Costa Rica - Flores Llampa, B. (2005)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2005